Implementasi Sistem Perizinan Berusaha Terintegrasi Secara Elektronik (Online Single Submission) Sebagai Upaya Meningkatkan Kualitas Pelayanan Publik Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Minahasa Tenggara - Marsela Fransisca Walangitan; Johnny A. F. Kalangi; Eveline J. R. Kawung (AGRI-SOSIOEKONOMI, 2022)
This study aims to describe or find out the implementation of an electronically integrated business licensing system (online single submission) in improving the quality of public services at the Southeast Minahasa One-Stop Investment and Services Agency. The research was located at the Investment and One Stop Service Office of Southeast Minahasa Regency as the research location. This study uses a qualitative approach to process the data obtained from the research location where the data is in the form of words, sentences, schemes or pictures. This research is a descriptive research, namely to find out or describe the reality of the events studied or research conducted on independent or single variables, without making comparisons or connecting with other variables. A total of 8 informants in this study were selected because they know the problems regarding the quality of public services. The data collected in this study is data that is in accordance with the research focus, namely verbal data which is information from related parties, which consists of primary data and secondary data. Data collection techniques used are observation, in-depth interviews, and documentation. Data analysis in this research is by data reduction, data display, and data conclusion/verification. The results obtained from the aspect of tangible is quite good but there are inadequate facilities and infrastructure, the aspects of reliability, responsiveness, assurance and empathy are appropriate as they should be.